Religijność i etyczne podstawy dialogu międzyreligijnego według Paula Ricoeura - Lubowicka, Grażyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The paper discusses Paul Ricœur’s concept of the religious as the unknowable source going beyond all historical religions and underpinning them all, but manifesting itself only through them. The religious can be apprehended and approached by means of interreligious dialogue, which Ricœur bases on the hermeneutic paradigm of translation. In the case of Judeo-Christian religions making common reference to revelation, interreligious dialogue also requires its participants to accept the ethical postulates derived from the theory of translation, which are linguistic hospitality, tolerance and self-criticism.
Keywords: interreligious dialogue; hospitality; Paul Ricoeur; religious; translation